Growth Rates and Correlations between some Growth Parameters of Sunflowers (Helianthus annuus L.) Irradiated Plants - Dafalla, Mashaeir F.; Kehail, Mutaman A.; Abashar, Abasher A.; Abdelrahim, Yassir M. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
Sunshine is a type of radiation that is needed for photosynthesis and normal plant growth, so, no all radiation is bad. This study aimed to evaluate the growth rates and correlation between them in sunflower (Helianthus annuus L.) irradiated with X-ray, Gamma-ray, and UV-light. The experiment was conducted in 2020, in the experimental farm, Faculty of Agriculture, University of Gezira, Sudan. A well-known variety of sunflower seeds were brought from Agricultural Research Corporation, Wad Medani, Gezira State, Sudan. The sunflower seeds were submitted separately to two treatments of X-ray (33.4 (LX) and 200.2 sec (HX), gamma-ray (200 (LG) and 800 cGy (HG)) and UV-light (for 30 sec. (UV)). In addition to control, all irradiated sunflower seeds were grown under the same environmental conditions. The growth parameters (plant weight, height, diameter, No. of leaves, tall, and width of leaves) were recorded every 10 days till 60 days. The results of this study revealed that LX sunflower plants have a daily increase in net weight of 0.24 g; 0.90 cm in stem tall; 0.03 cm in stem diameter; 0.12 cm in leaves tall; 0.06 cm in leaves width and 0.36 in leaves number, compared to 0.22 g in net weight; 1.10 cm in stem tall; 0.03 cm in stem diameter; 0.17 cm in leaves tall; 0.13 cm in leaves width and 0.36 in leaves number in C, white it was 0.09 g in net weight; 0.68 cm in stem tall; 0.01 cm in stem diameter; 0.04 cm in leaves tall; 0.01 cm in leaves width and 0.27 in leaves number in HG, which are relatively less than that of LX, HX and LG. Most of the growth parameters correlated to each other by a positive factor of more than (0.95). Further studies should be conducted to evaluate the nutritional contents and human allergic ability.